2003
DOI: 10.7326/0003-4819-139-1-200307010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Test Characteristics of α-Fetoprotein for Detecting Hepatocellular Carcinoma in Patients with Hepatitis C

Abstract: The paucity of high-quality data calls for more rigorous study of AFP and other diagnostic tests for detecting hepatocellular carcinoma in HCV-infected patients with an accepted gold standard applied to the entire cohort. Even if the "best-case" estimates of AFP sensitivity and specificity are accurate, AFP has limited utility for detecting hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
233
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(248 citation statements)
references
References 32 publications
7
233
0
8
Order By: Relevance
“…We ran another MEDLINE search using more specific terms (Appendix 2) and identified 985 additional articles to be reviewed. We also identified two systematic reviews on detecting HCC in patients with chronic hepatitis C [33,34] and checked their bibliographies. After reviewing titles and abstracts, 54 articles were retrieved for full-text evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We ran another MEDLINE search using more specific terms (Appendix 2) and identified 985 additional articles to be reviewed. We also identified two systematic reviews on detecting HCC in patients with chronic hepatitis C [33,34] and checked their bibliographies. After reviewing titles and abstracts, 54 articles were retrieved for full-text evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…During the literature-searching process, we identified two systematic reviews of the diagnostic accuracy of AFP [33,34]. Both of them focused on HCV-positive patients based on the concept that the natural history of hepatitis C is different from that of hepatitis B [6,40].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-fetoprotein (AFP), which is widely used in clinical practice, has low sensitivity and poor diagnostic yield at the early stage of HCC (reported sensitivity, 39-64%; specificity, 76-91%; positive predictive value, 9-32%) (4,5). Accordingly, new markers, which have higher sensitivity and specificity, are needed to improve the diagnosis at the early stage and potentially increase the survival.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and critical analysis of the literature, based on a Medline search from 1966 to 2002, indicated that for HCC screening, a serum AFP level >20 lg/L had a sensitivity of 41% to 65%, specificity of 80% to 94%, positive likelihood ratios of 3.1 to 6.8, and negative likelihood ratios of 0.4 to 0.6 for diagnosis of HCC. 23 This relatively poor performance, in addition to the unmet need for early HCC diagnosis, led us to a search for more sensitive and specific biomarkers of HCC. Because HCC is a highly vascular tumor, researchers have studied screening patients for markers of increased angiogenesis, which may be detected even before HCC is clinically manifest.…”
mentioning
confidence: 99%